Message frames and wildlife values influence public acceptance of wild horse management strategies - Rodriguez, Jeffrey, author; Bright, Alan, advisor; Niemiec, Rebecca, advisor; King, Sarah, committee member (Colorado State University. Libraries, 2020)
Wild horses are a symbol of the American West that evoke emotional responses from people, and the management of these populations has become a contentious issue. We examined the influence of messaging and wildlife value orientations on public acceptance of potential wild horse management actions in the Western United States. We used an online questionnaire that began with one of three randomly assigned messages about wild horse management: the control message provided information about wild horse populations and management options, the rational appeal added on information about the negative impacts of growing wild horse populations and the limitations of current management approaches, and the emotional appeal added a photograph of emaciated wild horses to the rational appeal. The questionnaire then asked participants about their acceptance of wild horse management options and their values of and experiences with domestic horses. Our survey experiment showed that messaging can influence overall acceptance of wild horse management techniques. Participants who received the emotional or rational appeal were more accepting of the use of contraception, sterilization, euthanasia, and the sale of horses to be used for consumption compared to those who received the control. Adding an emotional component to the rational appeal increased acceptance of wild horses living out their lives in government holding pens over all other message conditions. We also found that participants in general were more accepting of contraception and sterilization than any of the other management techniques. Participants with traditionalist values were more likely to accept euthanasia. Overall, we suggest that messaging may influence public acceptance of many of the proposed management actions for wild horses in the Western United States.
Keywords: communication; values; wildlife value orientations; messaging; attitudes; wild horse